Profiling Hydrodynamic Aspects of Finswimming Athletes: Biffins Relay Position - Sungkowo, Sungkowo; RAhayu, Tandiyo Rahayu; Widjanarko, Bambang; Setyanto, Taufiq Arif; Kusuma, Donny Wira Yudha; Kumbara, Agus Kristiyanto; Purakom, Atchara (Department of Physical Education, Sport, Health and Recreation, 2023)
One of the most significant aspects of diving is technical and physical analysis. As a result, this analysis must be conducted so that dive comprehension and learning become more effective and efficient. bi-finswimming movement and Speed testing approach in diving, on the other hand, necessitate specialised equipment. Furthermore, studies on hydrodynamic analysis in diving are still scarce in Indonesia. Thus, the objective of this research was to examine the hydrodynamics of bi-finswimming 4x100 metre bi-finswimming relay athletes. The descriptive quantitative research method was employed, along with a survey. Document analysis approaches, interviews as problem rationalisation and field tests were used to collect data. Four elite swimmers had been participated in this study. A resistance dynamometer and a Qualisys underwater camera were among the research tools. The data analysis technique used. According to the survey results, bi-fin swimmers have varied techniques that fall into three categories: effective, less effective, and ineffective. Understanding and mastering the bi-finswimming style can reduce drag, from the resistance dynamometer results, the data showed that each swimmer has differences in resistance with A position (straight arms), B position (left arm recovery), C position (right arm recovery) with speed of 1 m/h, 1,25 m/h, 1,50 m/h, 1,75 m/h, and 2 m/h respectively. Conclude that every finswimming swimmer has their own technique. By understanding and able to perform the proper technique, we believe that swimmers could minimalize the resistance and able to produce the bigger force.